Prognostic significance of calcium signaling-related genes in bladder cancer and the role of ATP2B4 in regulating mitochondrial calcium ion levels via the VDAC1/MCU pathway - Zhang, Lulu; Gong, Yu; Chen, Jiajun; Li, Mengyao; Wang, Xiurong; Wang, Weihao; Ding, Qiannan; Li, Yulei (Frontiers in Immunology, 2026)
BackgroundCalcium signaling, as a ubiquitous intracellular signal in eukaryotes, has been impacted in multiple biological processes encompassing tumorigenesis. Nevertheless, the integrated investigations on the function and prognostic value of genes correlated to calcium signaling in bladder cancer (BLCA) were still lacking.MethodsThe transcriptome data and clinical data from BLCA patients were obtained from TCGA and GEO databases. Genes associated with calcium signaling that are differentially expressed in normal and malignant tissues were identified. Cox analysis and the least absolute shrinkage and selection operator (LASSO) analysis were employed to identify prognostic genes and develop a prognostic signature. The tuning parameter (λ) for LASSO regression was determined by cross-validation. The outcomes were then confirmed using an external independent dataset (GSE32894). The prognostic signature’s reliability was assessed utilizing Kaplan-Meier, PCA, t-SNE, and ROC analyses. Furthermore, both univariate and multivariate Cox regression studies were undertaken to ensure if the prognostic signature functioned as an autonomous prognostic indication. Moreover, we examined the connection between the immune cell infiltration, the tumor mutation burden (TMB), and the prognostic signature. The Genomics of Drug Sensitivity in Cancer (GDSC) database and the IMvigor210 dataset were deployed to forecast the treatment reactions of the prognostic signature. Ultimately, the functionality of ATP2B4 was confirmed by in vitro and in vivo tests.ResultsThirty-two differentially expressed calcium signaling-correlated genes were identified in the TCGA dataset. A prognostic signature containing six genes (ATP2B4, BDKRB2, EDNRA, PDGFRA, EGFR, and ADCY7) was ascertained to anticipate the overall survival of BLCA. Furthermore, a nomogram containing risk scores with age was developed to anticipate the BLCA patient’s prognosis. In addition, patients among the high- and low-risk groups displayed significant variation in TMB, immune infiltration landscape, and response to chemotherapy and immunotherapy. ATP2B4 has been recognized as a pivotal oncogenic gene. The suppression of ATP2B4 results in elevated cytoplasmic calcium ion(Ca2+) concentrations, which in turn activate the VDAC1/MCU pathway. This activation facilitates the transfer of Ca2+ from the cytoplasm to the mitochondria, culminating in mitochondrial Ca2+ overload and ultimately inducing apoptosis in bladder urothelial carcinoma (BLCA) cells.ConclusionsCollectively, we have developed a unique genetic signature that is based on genes associated with calcium signaling. This signature possesses the capacity to precisely anticipate the survival prognosis and therapeutic response of BLCA patients and might have a crucial role in guiding clinical treatment. Furthermore, ATP2B4 has been identified as a crucial oncogenic gene. The downregulation of ATP2B4 leads to mitochondrial Ca2+ overload, ultimately resulting in apoptosis of BLCA cells.